Late gestation over‐ and undernutrition predispose for visceral adiposity in response to a post‐natal obesogenic diet, but with differential impacts on glucose–insulin adaptations during fasting in lambs. (25th June 2013) - Khanal, P.; Husted, S. V.; Axel, A. M. D.; Johnsen, L.; Pedersen, K. L.; Mortensen, M. S.; Kongsted, A. H.; Nielsen, M. O.
Abstract Aim To investigate if late gestation under‐ or overnutrition has similar adverse impacts on visceral adiposity, metabolic and endocrine function in sheep, and if subsequent exposure to a high‐fat diet in early post‐natal life exaggerates the prenatal programming outcomes later in life. Methods Thirty‐six twin‐pregnant ewes were fed a NORM (fulfilling 100% of daily requirements for energy and protein), LOW (50% of NORM) or HIGH diet (150% of energy and 110% of protein requirements) during the last 6 weeks of gestation (term = 147 days). Post‐natally, the twin lambs were subjected to a high‐fat or a moderate diet until 6 months of age (around puberty), where metabolic and endocrine adaptability to fasting was examined, and subgroups of animals were killed. Results Animals exposed to either prenatal under‐ or overnutrition had reduced subcutaneous fat deposition when fed a high‐fat diet, resulting in higher ratios of mesenteric and peri‐renal fat relative to subcutaneous fat compared to controls. This was not related to prenatal influences on plasma glucose or insulin. Irrespective of the prenatal diet, high‐fat‐fed lambs underwent changes resembling the metabolic syndrome with higher plasma glucose, cholesterol, non‐esterified fatty acids, triglyceride and lactate combined with abdominal obesity. Peri‐renal fat appeared to be a particular target of a high‐fat diet post‐natally. Conclusion Both prenatal under‐ and overnutrition predisposed for abdominal adiposity, apparently by reducing the expandability of subcutaneous adipose tissue and induced differential physiological adaptations to fasting. This study does not suggest that exposure to gestational overnutrition will provide a protective effect against development of hyperglycaemia later in life.